Radiotherapy in Combination With Cytokine Treatment - Palata, Ondrej; Hradilova Podzimkova, Nada; Nedvedova, Eva; Umprecht, Alexandra; Sadilkova, Lenka; Palova Jelinkova, Lenka; Spisek, Radek; Adkins, Irena (Frontiers in Oncology, 2019)
Radiotherapy plays an important role in the management of cancer patients. Radiotherapy is used in more than 50 % of patients during the course of their disease in a curative or palliative setting. In the past decades it became apparent that the abscopal effect induced by radiotherapy might be dependent on the activation on immune system and that the induction of immunogenic cancer cell death and production of danger-associated molecular patterns from dying cells play a major role in the radiotherapy-mediated anti-tumor efficacy. Therefore, the combination of radiotherapy and immunotherapy is of a particular interest that is reflected in designing clinical trials to treat patients with various malignancies. The use of cytokines as immunoadjuvants in combination with radiotherapy has been explored over the last decades as one of the immunotherapeutic combinations to enhance the clinical response to anti-cancer treatment. Here we review mainly the data on the efficacy of IFN-α, IL-2, IL-2-based immunocytokines, GM-CSF and TNF-α used in combinations with various radiotherapeutic techniques in clinical trials. Moreover, we discuss the potential of IL-15 and its analogues and IL-12 cytokines in combination with radiotherapy based on the efficacy in preclinical mouse tumor models.